Transcatheter Arterial Embolization for Shock Caused by Intratumoral Hemorrhaging in Neurofibromatosis Type 1: A Report of Two Cases - Hiroto Saijo; Kenji Hayashida; Shin Morooka; Kaoru Kuwabara; Masaki Fujioka (Karger Publishers, 2014)
Neurofibromatosis type 1 (NF-1) is an autosomal dominant disorder characterized by café-au-lait spots and neurofibroma. Vascular NF-1 lesions are rare, but bleeding from such lesions can sometimes cause lethal complications because surgical hemostasis is difficult to achieve due to the fragile nature of the surrounding blood vessels and soft tissue. In recent years, some reports have suggested that transcatheter arterial embolization (TAE) is an effective treatment for vascular NF-1 lesions. We report the cases of 2 NF-1 patients who developed intratumoral hemorrhaging and were successfully treated with TAE.